2005
DOI: 10.1207/s15374424jccp3404_14
|View full text |Cite
|
Sign up to set email alerts
|

Prevention for Preschoolers at High Risk for Conduct Problems: Immediate Outcomes on Parenting Practices and Child Social Competence

Abstract: This study investigated the immediate impact of an 8-month center-and home-based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 63 publications
4
97
0
2
Order By: Relevance
“…Several prevention curricula have demonstrated effectiveness against CD, substance use, or both, among children and adolescents (e.g., Bierman et al, 2002;Botvin and Kantor, 2000;Brotman et al, 2005;Conduct Problems Prevention Research Group, 2002;Farmer et al, 2002;Hawkins et al, 1999;). To our knowledge, however, their effects on fully diagnosable substance use disorders have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Several prevention curricula have demonstrated effectiveness against CD, substance use, or both, among children and adolescents (e.g., Bierman et al, 2002;Botvin and Kantor, 2000;Brotman et al, 2005;Conduct Problems Prevention Research Group, 2002;Farmer et al, 2002;Hawkins et al, 1999;). To our knowledge, however, their effects on fully diagnosable substance use disorders have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…This was a subsample of children (N ÂŒ 99) enrolled in a preventive intervention trial for preschoolers at risk for psychopathology (Brotman et al, 2005;Brotman et al, 2007). Only those children who were administered the EC Battery were included in our study.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Parent ratings were valence, responsiveness, warmth, praise, enjoyment, scaffolding, effectiveness, aggression and criticism/punishment. In previous work with high-risk preschool-age children, Brotman et al [3,4] reported adequate inter-rater reliability for the individual codes in the original GIPCI. Global ratings have been shown to be significantly related to behavioral counts of behaviors during the same interactions, and parenting constructs based on GIPCI global ratings have been shown to be sensitive to intervention effects [3,4].…”
Section: Direct Observation Of Mother-child Interactionsmentioning
confidence: 97%
“…In previous work with high-risk preschool-age children, Brotman et al [3,4] reported adequate inter-rater reliability for the individual codes in the original GIPCI. Global ratings have been shown to be significantly related to behavioral counts of behaviors during the same interactions, and parenting constructs based on GIPCI global ratings have been shown to be sensitive to intervention effects [3,4]. Using interclass correlations the average inter-rater reliability across all item codes in this study was adequate for child (intraclass correlation = 0.62; range 0.48-0.77) and parent (0.64; range 0.48-0.79).…”
Section: Direct Observation Of Mother-child Interactionsmentioning
confidence: 97%